2010
DOI: 10.1111/j.1464-410x.2010.09332.x
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer in cystoscopically normal‐appearing mucosa: a case of mistaken identity?

Abstract: Study Type – Diagnosis (exploratory cohort)
Level of Evidence 2bOBJECTIVETo test the frequency of malignancy in normal‐appearing urothelium in patients with high‐risk bladder cancer, as biopsy of normal‐appearing mucosa using standard white‐light cystoscopy (WLC) reportedly shows carcinoma in situ (CIS) in some patients with bladder tumours.PATIENTS AND METHODSCold‐cup biopsies of normal‐appearing mucosa were obtained by two experienced oncological urologists from 63 patients during transurethral resection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…In the setting of malignant voided cytology results it is important to have a low threshold for biopsy of indeterminate lesions but mucosa that appears endoscopically normal to an experienced urologist is rarely interpreted as malignant when examined by expert uropathologists. 9 Additionally, simply finding more cancers may not be a clinically important end point since the biological potential of an endoscopically imperceptible lesion is unclear. For example, early reports of fluorescent cystoscopy demonstrated that the technique identified more tumors than white light cystoscopy 10 but a phase III multicenter study showed no difference in RFS or disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of malignant voided cytology results it is important to have a low threshold for biopsy of indeterminate lesions but mucosa that appears endoscopically normal to an experienced urologist is rarely interpreted as malignant when examined by expert uropathologists. 9 Additionally, simply finding more cancers may not be a clinically important end point since the biological potential of an endoscopically imperceptible lesion is unclear. For example, early reports of fluorescent cystoscopy demonstrated that the technique identified more tumors than white light cystoscopy 10 but a phase III multicenter study showed no difference in RFS or disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…As CIS can often be found in normal‐looking mucosa, the traditional approach has involved taking cold‐cup biopsies to screen for CIS, and this procedure is frequently called BMAP. However, deciding when to take biopsies from apparently ‘normal’ bladder mucosa is a matter of debate [12]. The yield is low in patients harbouring small, solitary papillary tumours with unsuspicious cytology [13,14], whereas CIS can be found concomitantly in up to 59% of patients with high‐risk tumours and positive cytology [15].…”
Section: Discussionmentioning
confidence: 99%
“…An important limitation of the present study is that we lack information on which individual cold‐cup biopsies were taken from somewhat suspicious mucosa and which from totally normal‐looking mucosa. We are therefore unable to draw conclusions about the value of sampling entirely normal‐looking mucosa which has been questioned [12]. However, the sampling method used represents traditional approach for identifying CIS in suspected cases and each patient is his own control, which provides access to the ‘true’ occurrence of CIS in the pathology specimen, with the restrictions mentioned above.…”
Section: Discussionmentioning
confidence: 99%